The Spectacle of Matter Being Transformed - Perkins, Elizabeth (LiNQ (Literature in North Queensland), 2016)
Elizabeth Perkins reviews: Helen Gamer. Cosmo Cosmolino. Ringwood: McPhee Gribble Penguin Books, 1992. ISBN 0 86914 265 8. 221 pp. $29.95.